Fluorescence properties of dyes for 570-800 nm lasing region in sol-gel silica - Bezkrovnaya, O.N.; Maslov, V.V.; Pritula, I.M.; Puzikov, V.M.; Plaksiy, A.G.; Gurkalenko, Yu.A.; Lopin, A.V.; Pereverzev, N.V. (Functional Materials, 2015)
The spectral-fluorescence characteristics of the dyes for 570-800 nm lasing region: Rh6G, DCM, LD678, and Rh800 were studied with the purpose to clarify an influence of intermolecular interactions in SiO₂ matrix on processes of the excitation energy decay of the laser dyes in S₁ state. Their quantum yields Qfl and decay times τfl of fluorescence, radiative kr and non-radiative knr rate constants for solvents and matrices were measured and calculated. It was shown for the dyes with small solvent effect (Rh6G, LD678) that incorporation of them into the matrix did not cause the appreciable changes of Qfl and τfl values. While for the dyes with strong solvent effect (DCM and Rh800) - SiO₂ matrix takes the stabilizing influence upon their molecules in S₁ state and as a result their non-radiative losses were diminished and quantum yield was increased.